Innovation: the Central Issue of 21st Century Society. An Educational Quest to Modernize-Transform the School - MEJÍA, MARCO RAÚL (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
This article aims to explain the importance of innovation in the XXI Century educational processes, considering it as a fundamental practice in the modernization and transformation of the school; to do so, the author takes into account different elements which intervene in the development of innovation as a phenomenon that transcends today's’ cultural and social scenarios, from a comprehensive perspective, and he points out the disadvantages it faces on the school.